Comparative analysis of serum trace element levels in women with invasive cervical cancer in Lagos, Nigeria - Okunade, Kehinde Sharafadeen (Pan Afr Med J, 2018)
INTRODUCTION: Trace elements although present in minute quantities in human blood, they play a vital role in many biochemical enzymatic reactions and have been examined critically as a potential key factor in various human diseases including cancers. This study was aimed to determine the association between serum levels of trace elements and invasive cancer of the cervix. METHODS: This was an analytical cross-sectional study carried out among women seen at the Lagos University Teaching Hospital (LUTH). Fifty histologically diagnosed patients with squamous cells carcinoma of the cervix, who had not had any treatment and 100 cancer-free volunteers were recruited. A structured interviewer-administered questionnaire was used to collect relevant data following which venous blood sample was obtained from each participant. Serum zinc, copper and selenium concentrations were then measured. The associations of serum trace elements and invasive cervical cancer were tested using the independent sample t-test. All significances were reported at P<0.05. RESULTS: There were significantly low serum levels of zinc and selenium in cervical cancer patients with no significant difference seen in the serum level of copper among cervical cancer patients compared to their cancer-free control counterparts. CONCLUSION: These alterations in trace elements levels may be important in the pathogenesis of cervical cancers; however, future robust prospective studies are needed to determine if routine provision of these supplements will result in improved cervical cancer treatment outcomes in Nigerian women.